Designing tri-branched multiple-site SO2 capture materials. Issue 24 (7th June 2018) - Li, Chenchen; Lu, Dongmei; Wu, Chao
Abstract : Tri-branched species with multiple isolated reactive sites are proposed for high and uniform SO2 capture. Abstract : SO2 capture materials usually have multiple reactive sites located within a limited space, thus absorptions (or adsorptions) of disparate strengths and low effective capacity per sorption–desorption cycle become the natural results of the so-called "coverage effects" (due to both the electronic and steric effects). Here, we propose a tri-branched framework with separated reactive sites and nearly uniform charge distribution on the reacting atoms. Through density functional theory (DFT)-based calculations and simulated isotherms, two N-centered anionic structures (terminated with amine (TAEA ) and imidazolyl (TIA ) groups, respectively) are selected from a series of representative tri-branched species. TheTAEA -based ILs are predicted to exhibit the highest uptakes (about 6.1 mol SO2 per mole IL) at 1 bar of SO2 and 20 °C, which reach the ceiling capacity that a negative charge can provide. TheTIA -based ILs have small differences in their SO2 sequential binding energies and they are estimated to have the best effective SO2 capacity during a sorption–desorption cycle (about 2.6 mol SO2 per mole IL, absorption at 1 bar of SO2 and 20 °C and desorption at 1 bar of SO2 and 120 °C). Moreover, we also find that the designed species can efficiently capture other gases like NO.